Identification of University Teachers’ Academic Commitment in Personality Development towards Academic Excellence - Shafqat, Saira; Zafar, Jam Muhammad; Bhadroo, Mazhar Hussain (Annals of Human and Social Sciences, 2024)
The main objective of the present study was to identify the university teachers’ academic commitment in personality development towards academic excellence. The study was survey and descriptive in nature. The quantitative and qualitative method were adopted. The explanatory sequential technique was used. Population of study comprised; Chairpersons/ HODs, faculty members of various departments of KFUEIT Rahim Yar Khan. The random sampling technique was used. The sample of study comprised of Chairpersons/ HODs/ Directors, 40 Faculty members 280 and total sample was 320. The interviews were recorded personally by the researcher which was a primary source of data. The questionnaire consisted of closed-ended and open-ended parts were used. The validity and reliability of tools were used for pilot testing. The study concluded that majority of HODs and Teachers don’t teach actively in well-spaced and fully air-conditioned classroom. The study recommended that well-spaced and fully air-conditioned classrooms may be provided in the public sector universities of Pakistan.